217k views
4 votes
What’s the answer?? (SOMEONE PLEASE HELP ME)

What’s the answer?? (SOMEONE PLEASE HELP ME)-example-1
User Bergy
by
5.1k points

1 Answer

1 vote

x = 6 or x = - 1

rearrange the equation into standard form and factorise

subtract ( - 2x - 4 ) from both sides

x² - 5x - 6 = 0 ← in standard form

the factors of - 6 which sum to - 5 are - 6 and + 1

(x - 6)(x + 1) = 0

equate each factor to zero and solve for x

x - 6 = 0 ⇒ x = 6

x + 1 = 0 ⇒ x = - 1



User Vitor Silva
by
4.7k points